2017
DOI: 10.2174/1573406413666170726142949
|View full text |Cite
|
Sign up to set email alerts
|

In vitro α-Glucosidase Inhibition by Non-sugar based Triazoles of Dibenzoazepine, their Structure-Activity Relationship, and Molecular Docking

Abstract: Among the reported triazoles, compounds 3-9, 11, and 13 (IC50 = 6.0 ± 0.03 to 19.8 ± 0.28 µM) were found to be several fold more active than the standard drug acarbose (IC50 = 840 ± 1.73 µM). Compound 5 (IC50 = 6.0 ± 0.03 µM) was the most potent AGIs in the series, about 77- fold more active than acarbose. Therefore, dibenzoazepine linked-triazoles described here can serve as leads for further studies as new non-sugar AGIs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The LAB helps to induce an immune response and reduce/inhibit the pathogens through several mechanisms. Many studies reported α-glucosidase inhibition activity ( Khan et al, 2017 ), production of bacteriocins (protein compounds) which have antagonistic potential against pathogenic bacteria, and a different degradation system in the digestive system ( Hawaz, 2014 ). Hernández-González et al (2021) also studied the antimicrobial, probiotics, and immunomodulatory potential of LAB in veterinary medicine.…”
Section: Introductionmentioning
confidence: 99%
“…The LAB helps to induce an immune response and reduce/inhibit the pathogens through several mechanisms. Many studies reported α-glucosidase inhibition activity ( Khan et al, 2017 ), production of bacteriocins (protein compounds) which have antagonistic potential against pathogenic bacteria, and a different degradation system in the digestive system ( Hawaz, 2014 ). Hernández-González et al (2021) also studied the antimicrobial, probiotics, and immunomodulatory potential of LAB in veterinary medicine.…”
Section: Introductionmentioning
confidence: 99%
“…At present, α-glucosidase inhibitors have been marketed as therapeutic drugs for T2DM, including acarbose [ 10 ], voglibose [ 10 ], and miglitol [ 11 ], and have been used in reducing plasma glucose levels and postprandial hyperglycemia ( Figure 1 ) [ 12 ]. However, their widespread application has been limited by the complicated multistep procedures needed for their synthesis and undesirable side effects such as gastrointestinal intolerability, diarrhoea and flatulence [ 13 ]. Therefore, the search for new small molecules possessing potent α-glucosidase inhibitory activity and minimal side effects has attracted significant attention for many years.…”
Section: Introductionmentioning
confidence: 99%
“…Basha group has published few reports on α-glucosidase inhibition by triazole analogues XI-XII (Figure 2). [4,[31][32][33] In reference to the biological importance of sultams, and fluorine in medicinally important compounds, and literature precedence on α-glucosidase inhibition of triazole analogues (shown in Figures 1and2), [4,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] new F-based sultam triazoles were designed, and screened for their α-glucosidase inhibitory activities to find new and safer hits for the management of diabetes. All the synthesized sultam triazoles are identified as new compounds, and this is their first report for inhibition of αglucosidase enzyme in vitro.…”
Section: Introductionmentioning
confidence: 99%